Hvad er revolutionær litteratur? - Ohldieck, Hans Jacob (Passage - Tidsskrift for litteratur og kritik, 2010)
Hans Jacob Ohldieck: "Hvad er revolutionær litteratur? - Om nybarokken som tænkning og litterært udtryk i lyset af Den cubanske revolution" Abstract Hans Jacob Ohldieck: “What is Revolutionary Literature? On Neobaroque as Thought and Literary Expression in Light of the Cuban Revolution” The article discusses two contrasting conceptions of revolutionary literature in the aftermath of the Cuban revolution of 1959: the “revolutionary novel”, drawing on a tradition of realism and an epic underpinning of the revolutionary project, and neobaroque, of which Cuban author Severo Sarduy created a theoretical framework on the basis of José Lezama Lima’s novel Paradiso. Through the figure of Sarduy, the dominant aesthetics of the Cuban literary sphere of the 60’s was confronted with a neobaroque theory with a radically different view on the characteristics of revolutionary literature.